2020
DOI: 10.5539/ies.v13n3p111
|View full text |Cite
|
Sign up to set email alerts
|

Study on Emotional Intelligence Levels of Physical Education Teachers in Terms of Various Variables

Abstract: For teaching profession, one of the important types of intelligence is emotional intelligence. Emotional intelligence levels of especially physical education teachers are expected to be high. The aim of this study is to examine emotional intelligence levels of physical education and sports teachers based on various variables. In this research, single screening model which is one of the General Survey models has been adopted. Population of the study consists of 320 Physical Education Teachers working in Ağrı in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The reason for such interest lies in the fact that empirical research has consistently shown that emotional and cognitive factors play a crucial role in influencing athletes’ performance and career trajectory [ 1 , 2 , 3 , 4 , 5 ]. Indeed, through the integration of physical, cognitive, and emotional aspects, athletes can attain the intended degree of psychological equilibrium and optimize their performance [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reason for such interest lies in the fact that empirical research has consistently shown that emotional and cognitive factors play a crucial role in influencing athletes’ performance and career trajectory [ 1 , 2 , 3 , 4 , 5 ]. Indeed, through the integration of physical, cognitive, and emotional aspects, athletes can attain the intended degree of psychological equilibrium and optimize their performance [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%